INFLUENTIAL FACTORS TOWARDS TAX AVOIDANCE BY COMPANY SIZE AS CONTROL VARIABLE IN MINING COMPANY LISTED ON INDONESIAN STOCK EXCHANGE - lubis, juni eriaty (International Journal of Public Budgeting, Accounting and Finance, 2018)
This research was constituted the background for the issue and phenomena of tax avoidance in Indonesia. The objective of the research was to analyze the influence of business strategy, profitability, and leverage on tax avoidance, in the research firm size as the variable of control. The research used quantitative design, and the samples were 34 companies, taken by using purposive sampling technique. Secondary data were obtained from mining companies listed in the Indonesia Stock Exchange in the period of 2014-2016 and analyzed by using multiple linear regression analysis. The result of the research showed that business strategy, profitability, and leverage simultaneously had significant influence on tax avoidance in mining companies listed in the Indonesia Stock Exchange in the period of 2014-2016. Business strategy and profitability partially had positive and significant on tax avoidance, while leverage partially did not have any significant influence on tax avoidance. Firm size as the variable of control had positive and significant influence on tax avoidance